Patient's Utilization of Primary Care: A Profile of Clinical and Administrative Reasons for Visits in Israel - Tamar Adar; Inbar Levkovich; Orit Cohen Castel; Khaled Karkabi (SAGE Publishing, 2017)
Background: Data on patients' utilization of health services in primary care is relevant to planning healthcare. Data may be collected by numerous methods, but obtaining a true picture of content of care has practical difficulties. Objectives: To describe patient's reasons for visits to primary care physicians (PCPs) as presented by the patient; and to examine the effect of patient-, doctor- and clinic-related variables on the reasons for the visit. Methods: Visits to PCPs were observed by peer doctors during 2014, at primary care clinics in Israel. Data were collected on characteristics of physicians, patients, clinics, type of visit, and reasons for visit. Results: Eleven physicians from 7 clinics participated in the study. Data were gathered from 327 visits. Patients visited for a wide variety of reasons. The most common acute complaints were upper respiratory symptoms, gastrointestinal, skin symptoms, and back and neck problems. The most common chronic complaints were hypertension and diabetes. Patients presented with administrative requests in 36% of visits; 15% were for solely administrative issues. A total of 26.6% of visits included requests for blood tests or discussion of tests. Patients initiated preventive medicine issues in 5% of visits. Visits for chronic problems were directly correlated with patient age and the extent of acquaintance with the physician. Gender-associated differences were also found: women were more likely to visit for a new medical problem than men, while men were more likely to visit for known or chronic problems. Conclusions: Patients visit their PCP for a wide variety of reasons, often during the same visit. Patients refer for administrative requests in about a third of visits. They initiate preventive care infrequently (1 out of 20 visits). To further characterize patient utilization of primary care, a broader study needs to be performed.